The Prevalence of Temporomandibular Disorders in Patients Referred to the Prosthodontics Department of Shahid Beheshti Dental School in Fall 2010 - Tabatabaian, Farhad; Saboury, Abolfazl; Kaseb Ghane, Hadi (Journal of Dental School, 2020)
Objective: Temporomandibular disorders (TMDs) are among the most common disorders of the maxillofacial region and are often characterized by pain and dysfunction of the temporomandibular joint(TMJ) and muscles of mastication. Due to the presence of several diagnostic criteria for such disorders, the reported prevalence rates for TMDs have been variable in different communities. The aim of this study was to determine the prevalence of TMDs in patients presenting to the Prosthodontics Department of Shahid Beheshti Dental School (SBDS) in fall 2010. Methods: In this descriptive study, 150 patients presenting to the Prosthodontics Department of SBDS (86 females and 64 males) were randomly selected and evaluated by using a questionnaire (subjectively) and clinical examinations (objectively). Presence and prevalence of various symptoms of TMDs such as clicking and tenderness on palpation in the muscles of mastication and the TMJ were evaluated in patients. Statistical comparisons were carried out using chi-square test. Results: Clicking, masticatory muscle and joint tenderness, TMDs, and limitation of mouth opening were found in 21.3%, 18.7%, 5.3%, 18.7% and 1.3% of patients, respectively. Despite the higher prevalence of TMDs in females, the difference in this regard between males and females was not statistically significant (39.3% in men versus 60.7% in women). Conclusion: Based on the obtained results, the prevalence of TMDs and its related symptoms was 18.7% in patients presenting to the Prosthodontics Department of SBDS in fall 2010. This value was lower than the rates reported in the literature.